Penerapan Aplikasi Aminin untuk Meningkatkan Kemampuan Membaca Al-Qur’an Siswa Di MIS Nurul Falah Aceh Barat - Rahmat Saputra; Ade Mustadar; Putri Rahmawati (Genderang Asa: Journal of Primary Education, 2022)
This research aims to determine how the application of Aminin Application in improving the ability to reading the Qur'an in class V MIS Nurul Falah West Aceh and to find out how the effectiveness of the application of Aminin Application in improving the ability to read the Qur'an in class V MIS Nurul Falah West Aceh. This research is a Classroom Action Research (CAR) which is carried out in the form of an cycle in which there are four main stages of activity, planning, action, observation, and reflection, with data collection techniques are observation, tests and documentation. The results showed that the students' ability to read the Qur'an using the Aminin application was very effective in improving the students' reading skills of the Qur'an in class V MIS Nurul Falah Aceh Barat. This is evidenced by the increasing percentage of students' ability to read the Qur'an in each cycle. By using several stages of the cycle, namely pre-cycle, cycle I, and cycle II. In the pre-cycle of 27 students there were 5 students who completed or (18.51%) and 22 students did not complete (81.49%), while in the first cycle of 27 students there were 9 students who completed or (33.33%) and 18 students who did not complete (66.67%). Furthermore, in the second cycle, it showed that there was a very significant increase in the students' ability to read the Qur'an, namely from 27 students there were 26 students who completed or (96.30%) and only 1 student who did not complete (03.70%).